METHODOLOGICAL ISSUES OF THE FOLKLORE CIRCLE ORGANIZED IN EDUCATIONAL INSTITUTIONS - Hamrayeva U., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
Formation of general musical culture of students in "Music culture" classes of secondary schools depends on many factors, including listening to music, singing, theoretical literacy (acquiring theoretical information). takes the main place. In this sense, the activities of listening to music within these factors are expressed in almost all activities. In this article, the importance of the analysis of works in the acquisition of music-theoretical knowledge for students by listening and analyzing music is widely explained